Hoya species of Belitung Island, Indonesia, utilization and conservation - SRI RAHAYU; YULIAN FAKHRURROZI; HIRMAS FUADY PUTRA (Biodiversitas Journal of Biological Diversity, 2018)
Rahayu S, Fakhrurrozi Y, Putra HF. 2018. Hoya species of Belitung Island, Indonesia, utilization and conservation. Biodiversitas 19: 369-376. Epiphyte greatly contributing to the forest biomass in the tropic. Heath forest as occurred in Belitung Island, Indonesia is a specific habitat for many endemic species, which are poor in nutrients and very fragile in response to any disturbance. We observed Hoya species-one of the epiphytic genus in the tropic in the heath forest and on other habitats of Belitung Island, Indonesia. Hoya species are plants with promising uses as functional ornamental plants (able to absorb pollutants from their growing environments), and as sources of certain medicinal and pharmaceutical compounds. A survey of Hoya was carried out on Belitung Island, off the southeast coast of Sumatra, in 2015, 2016 and 2017. There are two interesting Hoya species that grow well in the "padang community" of the heath forest, on the island: i.e. H. coronaria Blume and H imperialis Lindl. These two have attractive flower size and color. Another species, H. verticillata (Vahl) G.Don, with less attractive flower color, is distributed in the mixed forest of the beach areas, while H. multiflora Blume and H. scortechinii King & Gamble, also with less attractive flower color, are distributed in mixed forest of upper elevations. The distribution and habitat preference of different Hoya species indicate different requirements for moisture and temperature, which we hypothesize also result in differences in the pollinator species visiting the plants. The "padang community" of the heath forest on Belitung experiences maximum temperatures up to 370C in the afternoon. It is located in an Af climate type, with average rainfall, air temperature and humidity of ± 205 mm/month, 270C and 77.5%, respectively. Hoya coronaria is the most contributing biomass in the heath forest compared to the other Hoya species in the community.